1998
DOI: 10.1182/blood.v91.9.3134.3134_3134_3143
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Knocked-In AML1-ETO Leukemia Gene Inhibits the Establishment of Normal Definitive Hematopoiesis and Directly Generates Dysplastic Hematopoietic Progenitors

Abstract: The t(8;21)-encoded AML1-ETO chimeric product is believed to be causally involved in up to 15% of acute myelogenous leukemias through an as yet unknown mechanism. To directly investigate the role of AML1-ETO in leukemogenesis, we used gene targeting to create anAML1-ETO “knock-in” allele that mimics the t(8;21). Unexpectedly, embryos heterozygous for AML1-ETO(AML1-ETO/+) died around E13.5 from a complete absence of normal fetal liver–derived definitive hematopoiesis and lethal hemorrhages. This phenotype was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(79 citation statements)
references
References 37 publications
4
73
0
1
Order By: Relevance
“…However, there was no significant difference in expression levels of AML1 and SCL mRNA in CD34-positive cells between aplastic anaemia patients and normal subjects in contrast to GATA-2. AML1 was the most common gene involved in acute myelogenous leukaemia, in which myeloid differentiation was blocked by a disturbance of the proper function of AML1 by the fusion protein AML1-ETO (Okuda et al, 1998). It has also been shown that the expression of SCL was upregulated along with erythroid differentiation (Elwood et al, 1998;Valtieri et al, 1998), consistent with the result in this study that SCL mRNA expression was lower in the CD34-positive fraction than in the CD34-negative fraction.…”
Section: Discussionsupporting
confidence: 89%
“…However, there was no significant difference in expression levels of AML1 and SCL mRNA in CD34-positive cells between aplastic anaemia patients and normal subjects in contrast to GATA-2. AML1 was the most common gene involved in acute myelogenous leukaemia, in which myeloid differentiation was blocked by a disturbance of the proper function of AML1 by the fusion protein AML1-ETO (Okuda et al, 1998). It has also been shown that the expression of SCL was upregulated along with erythroid differentiation (Elwood et al, 1998;Valtieri et al, 1998), consistent with the result in this study that SCL mRNA expression was lower in the CD34-positive fraction than in the CD34-negative fraction.…”
Section: Discussionsupporting
confidence: 89%
“…This strategy resulted in the expression of the chimaeric gene from the endogenous AML1 regulatory sequences, thus accurately mimicking the t(8;21). Under these conditions, expression of AML1-ETO produced an embryonic lethal phenotype that was almost identical to the one observed after the loss of AML1 or CBFb (Yergeau et al, 1997;Okuda et al, 1998). This result formally demonstrates that AML1-ETO can function as a dominant inhibitor of normal AML1/CBFb activity.…”
Section: The Aml1-eto Chimaeric Protein: Mechanisms Of Cell Transformsupporting
confidence: 61%
“…Direct proof of the role of AML1-ETO in haemopoietic cell transformation has come from experiments in which an AML1-ETO chimaeric gene was created by knocking ETO into the AML1 genomic locus (Yergeau et al, 1997;Okuda et al, 1998). This strategy resulted in the expression of the chimaeric gene from the endogenous AML1 regulatory sequences, thus accurately mimicking the t(8;21).…”
Section: The Aml1-eto Chimaeric Protein: Mechanisms Of Cell Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the AML1 dosage influences the fate of the haematopoietic progenitor cells, determining whether they self-renew or commit to differentiation. To support this possibility, haematopoietic progenitors that harbour engineered AML1-MTG8 allele(s) have been shown to have an increased potential for self-renewal (Okuda et al, 1998;Rhoades et al, 2000;de Guzman et al, 2002;Mulloy et al, 2002;Schwieger et al, 2002). In addition, multipotent haematopoietic stem cells appeared at earlier stages of development in AML1-haplo-insufficient mice, compared with the time they appeared in wild-type mice (Cai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%